Sliding Wear of the Ti-Reinforced Al Matrix Bi-metal Composite: A Potential Replacement to Conventional SiC-Reinforced Composites for Automotive Application - Gecu, Ridvan; Karaaslan, Ahmet (SPRINGER INT PUBL AG, 2019)
The automotive industry needs the combination of lightweight and high-strength materials which can be achieved by using aluminum matrix composites (AMCs). Production problems and expensiveness of conventional ceramic reinforced AMCs can be overcome by the use of metals as reinforcements. This study intends to demonstrate the potential of commercially pure titanium-reinforced A356 alloy matrix bi-metal composite for replacement of SiC-reinforced AMCs in automobile components. Ti-reinforced and SiC-reinforced A356 matrix composites were separately manufactured by melt infiltration casting. Porous monoblock preforms of Ti and SiC were infiltrated by molten A356 under vacuum atmosphere. Ball-on-disk tests were performed by using a 3-mm-diameter Al2O3 ball to determine relatively severe wear behavior of composites after production. The Ti-reinforced AMC showed better performance against wear under favor of TiAl3 formation at Al/Ti interface. Moreover, wetting problems occurred in the SiC-reinforced AMC, while good metallurgical and mechanical bonding was achieved in the Ti-reinforced sample. The feasibility of environmentally-friendly low-cost manufacturing of the Ti-reinforced A356 alloy matrix bi-metal composite has been demonstrated.
Keywords: bi-metal composite; wear; A356 alloy; commercially pure titanium; SiC particles; automobile components; MECHANICAL-PROPERTIES; GRAPHITE FIBER; HEAT-TREATMENT; TITANIUM; MICROSTRUCTURE; FABRICATION; BEHAVIOR; ALLOY; Metallurgy & Metallurgical Engineering